Perceptions of dental outpatients toward cross-infection control measures in Jabalpur city - Suryakant C Deogade; Sneha S Mantri; K Sumathi; Gunjan Dube; Jaiprakash R Rathod; Dinesh Naitam (Wolters Kluwer Medknow Publications, 2016)
Introduction: Infection control practices are crucial and important elements in clinical dentistry as there is an enormous increase in the prevalence of infectious diseases among dental patients. This necessitates the application of recommended procedures for infection control in the dental schools and clinics. Aim: The aim of this study was to assess patients' perception toward the use of protective barriers (such as gloves, face masks, and eye goggles) by working dentists in a private dental teaching school in Jabalpur, Madhya Pradesh (India). Materials and Methods: A cross-sectional descriptive study of a convenient sample of patients visiting the dental school of RDU was conducted in 2015. A structured, close-ended, self-administered questionnaire was distributed among 700 patients and a response rate of 89% was obtained. The questionnaire consisted of a series of questions related to awareness, knowledge, attitude, and perception of patients toward infection control measures. Data analysis included frequency distribution tables. Results: Of 664 patients (298 males and 366 females), 97.7%, 93.5%, and 43.6% of the patients believed that dentist should wear gloves, face masks, and eye goggles, respectively, when treating patients. The majority of them (95.3%) refused to undergo treatment if the dentist is not wearing gloves and face masks. More than two-thirds (73.3%) denied receiving treatment from a dentist, who is not immunized against hepatitis B. Nearly 79.2% of patients refused to attend school if they knew that human immunodeficiency virus (HIV) and hepatitis B virus (HBV) patients treated there. The majority of patients (92.7%, 72.3%, and 23.1%) believed that gloves, facemasks, and eye goggles protect both dentist and patient, respectively. Only 44.9% said that autoclave is the best method of sterilization. A significantly higher knowledge of infection control was observed among the previous dental visitors compared to the first-time visitors (P < 0.05). Conclusions: Patients revealed adequate knowledge toward the use of gloves, face masks, and eye goggles by a dentist. However, their knowledge regarding the use of autoclave was poor. This documentation will serve in planning more effective interventions to enhance public awareness about infection control in dentistry in Jabalpur city, India.